Reading on Your Own: An Extensive Reading Course - Barrett, Mary Ellen (Boston Heinle and Heinle Publishers, 1992)
Reading On Your Own is designed for high-intermediate to advanced learners of English as a second language. This course is designed for students to choose their own reading material from different sources and then read on their own. By using the approach presented in this text, students become empowered to read with more ease and confidence materials written for native speakers of English.
Keywords: Reading